ICT as an Engine for Uganda’s Economic Growth: The Role of and Opportunities for Makerere University - Baryamureeba, Venansius (Fountain Publishers Kampala, 2007)
The use of Information and Communications Technologies (ICT) to improve how goods are produced and services are delivered is a feature of everyday life in developed countries. If ICT is used appropriately, it has the potential to vastly improve productivity. Thus the issue for developing and least developed countries is how best to use ICT to achieve development objectives, given the operating constraints in these countries. The constraints are mainly lack of infrastructure and human capacity. It is now a known fact that ICT infrastructure readiness without adequate skilled ICT human capacity cannot lead to economic growth. In this paper we discuss the role of Makerere University and suggest opportunities for Makerere University in this area of ICT led –economic growth of Uganda.
Keywords: ICT; Engine; Uganda’s Economic Growth; Opportunities; Makerere University